1958
DOI: 10.1161/01.res.6.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Parenterally Administered Pyridoxine to Influence Serum Cholesterol Levels and Development of Atherosclerosis in Cholesterol-Fed Rabbits

Abstract: Pyridoxine administered parenterally was found to have no effect on serum cholesterol levels of rabbits fed a normnl diet, nor did it inhibit the development of hypercholesterolemia and atherosclerosis in rabbits fed a cholestercl-rich diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1959
1959
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…The findings of the above workers in monkeys and dogs along with knowledge of the role of vita min B^ in essential fatty acid metabolism led Schroeder (1955) to speculate on a combined role of pyridoxine and the essen tial fatty acids in the etiology of human atherosclerosis. He suggested that the American diet is marginal in pyridoxine and contains large amounts of saturated animal and hydrogenated vegetable fats which may be in part responsible for the high incidence of hypercholesteremia and atherosclerosis in the United States.The results obtained by other workers from similar lines of study are not entirely in agreement with the findings of the above workers Marten and Hoskins (1958). studied the in fluence of pyridoxins administration to cholesterol-fed rab bits on serum cholesterol levels and development of athero sclerosis.…”
supporting
confidence: 68%
“…The findings of the above workers in monkeys and dogs along with knowledge of the role of vita min B^ in essential fatty acid metabolism led Schroeder (1955) to speculate on a combined role of pyridoxine and the essen tial fatty acids in the etiology of human atherosclerosis. He suggested that the American diet is marginal in pyridoxine and contains large amounts of saturated animal and hydrogenated vegetable fats which may be in part responsible for the high incidence of hypercholesteremia and atherosclerosis in the United States.The results obtained by other workers from similar lines of study are not entirely in agreement with the findings of the above workers Marten and Hoskins (1958). studied the in fluence of pyridoxins administration to cholesterol-fed rab bits on serum cholesterol levels and development of athero sclerosis.…”
supporting
confidence: 68%
“…Although I already mentioned the experiments made by Faily and Dann in chicken, Martens et al 16) reported that pyridoxine had no influences on serum cholesterol and the development of atherosclerosis in the rabbits fed cholesterol. I noticed some preventive effects of PAL-PO4 and pyridoxamine phosphate (PAM-PO4) on the atherosclerosis of the rabbits fed lanolin 5mg.…”
Section: Prophylaxis and Treatment Of Experimental Atherosclerosis Wimentioning
confidence: 97%
“…In fact, there appeared to be an enhancement of the lesions. Martens and Hoskins (1958) observed no effect due to parenterally administered pyridoxine on the serum cholesterol levels of rabbits when they were fed a stock ration. When a cholesterol-rich diet was fed, the parenterally administered pyridoxine had no effect on the degree of hypercholesterolemia nor on the degree of atherosclerosis.…”
Section: Metabolic Relationships Of Vitamin Bgmentioning
confidence: 84%